70 Years of China's Bridges - Xiang, Zhongfu; Xu, Wei.; Liu, Anshuang; Meng, Fanchao (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book takes time as the axis, selecting 98 bridges (or bridge groups) across the country and 7 representative bridges out of the country, reflecting the steps and development of China's bridge construction in related majors and engineering technicians in colleges and universities. This book aims to let the general public understand the arduous history of China's bridge construction and the rapid development of China's bridge construction without the country's economic development, strength, and hard work of the bridge people. It is also hoped that the public will enjoy the convenience of bridges, highways, railroads, and urban roads and at the same time enhance their awareness of bridge knowledge, knowledge, love, and scientific use of bridges. This book is used by the general public to understand the development of China's bridge construction, but also as a reference book for teachers and students of bridge engineering-related majors and engineering technicians in colleges and universities.
Chapter 1 The Origin and Development of Bridges -- Chapter 2 Using Foreign Experience for Reference and Laying a Foundation for Further Bridge Development -- Chapter 3 Taking Full Advantage of Local Materials and Innovating in Bridge Technology -- Chapter 4 Learning Advanced Technology and Starting Rising -- Chapter 5 Rapid Development and Becoming a World Power in the Number of Bridges. Chapter 6 Making Technological Breakthrough and Becoming a World Power in Bridge Technology -- Chapter 7 Entering Foreign Lands and Becoming Established on the World Stage -- Chapter 8 Looking Back at the Past whilst Looking Forward to the Future.
Keywords: Technology; History; Engineering design; Materials; Statics; Sustainable architecture; History of Technology; Engineering Design; Materials Engineering; Mechanical Statics and Structures; Sustainable Architecture/Green Buildings